A Brief Introduction to Gurukul Education - Adhikari, Toya Nath (Pragya Darshan प्रज्ञा दर्शन, 2023)
This paper presents gurukul system of education as the main concern in the quality of human beings. Education is the only means of civilizing ourselves to maintain high qualities of integrity, devotion, sincerity and an ethical and moral purpose in our national life. The goal of our national education should be to supply a constant stream of knowledge, character, fearless open minded, truthful, and patriotic people, who will become the basic material, for building up the nation. Gurukul Style of Education system is a 5000-year old Hindu tradition of transmitting higher knowledge and enlightenment to the students by yogic powers by the guru with an aim to develop the latent yogic powers of the child and build him up into a moral and spiritual power.